Study on adverse effects of COVISHIELD vaccine among hospital employees of Nepal Medical College and Teaching Hospital (Nepal Medical College Journal, 2022)
Nepal government provided COVISHIELD vaccine first to the hospital employees and other front liners in January 2021. The objective of our study was to observe the adverse effects of the COVISHIELD among hospital employees of Nepal Medical College and Teaching Hospital (NMCTH). This was a descriptive cross-sectional study conducted from March to August 2021. The study was commenced after obtaining ethical clearance from the Institutional Review Committee of NMCTH. Self-reported socio-demographic details and symptomatic adverse effects reported after the first and second dose of COVISHIELD were noted. The data were entered in SPSS 16 and analysed. Out of 436 participants, 360 (82.6%) and 243 (55.7%) had reported adverse effects after the first and second dose of the COVISHIELD respectively. The adverse effects reported following COVISHIELD were common and predictable.